Numerical investigation of heat reduction system in 42110 Lithium-Ion battery packs using cooling plate spacing variations - Bima Rakha Adhitama; James Julian; Fitri Wahyuni; Fathin Muhammad Madhudhu; Elvi Armadani (Politeknik Negeri Lhokseumawe, 2025)
An efficient thermal reduction system is crucial for ensuring the optimal performance and safety of Electric Vehicle (EV) batteries, notably by maintaining uniform temperature distribution and minimizing the risk of thermal runaway. This study presents a numerical investigation of the thermal behaviour of a liquid-cooled system for a cylindrical Li-ion 42110 battery pack, focusing on the influence of varying cold-plate spacing. Three cold plate configurations with spacing ratios r = 0.78, r = 0.33, and r = 0 were examined, with r = 0.78 corresponding to the most significant separation. The simulation employed a Reynolds-Averaged Navier–Stokes (RANS) model to resolve fluid flow and energy transport, and the heat-generation profile was derived from experimental data. The results show that all cooling configurations substantially reduced the maximum temperature relative to the uncooled case, with the widest spacing (r = 0.78) achieving the most significant average reduction of 19.736%. However, designs with smaller spacing exhibited slightly higher temperatures and reduced uniformity, particularly near the positive pole, where heat concentration is more pronounced. The temperature deviation remained within the acceptable 2% threshold. These findings highlight not only the thermal effectiveness of each spacing ratio but also its design implications, demonstrating that spacing plays a critical role in controlling peak temperature and maintaining uniformity. Overall, the study emphasizes that strategic cold-plate spacing is essential for reliable, efficient, and thermally stable battery operation in EV applications.